Pengaruh Ice Breaking Terhadap Minat Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas V SD Negeri 29 Pardomuan di Kabupaten Samosir Tahun Pembelajaran 2023/2024 - Eva Silalahi; Rida Gultom; Pestaria Naibaho (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The purpose of this study is to determine how much influence Ice Breaking has on the Interest in Learning Christian Religious Education and Ethics of Class V Students of SD Negeri 29 Pardomuan I Learning Year 2023/2024. The research method used is descriptive quantitative method. The population is all grade V students of SD Negeri 29 Pardomuan I Learning Year 2023/2024 as many as 35 people. Data was collected using a positive closed questionnaire of 40 items, namely 25 items for variables X and 15 item for variable Y. The results of data analysis show that: a) positive relationship test obtained value rxy = 0.626 > rtabel(a=0.05,n=35) = 0.334 thus it is known that there is a positive influence between variable X and variable Y. b) Significant relationship test obtained tcount value = 4.617 > ttable(a=0.05,dk=n-2=33) = 2.042 thus there is a significant relationship between variable X and variable Y. c) Regression equation test, obtained regression equation . d) Regression coefficient of determination test (r2) = 39%. e) Test the hypothesis using the F test obtained Fcalculate > Ftable=(a=0.05,dk numerator k=13,dk denominator=n-2=35-2=33) which is 20.58 > 2.09. So it can be concluded that there is a positive and significant influence of Ice Breaking on the Interest in Learning Christian Religious Education and Ethics of Class V Students of SD Negeri 29 Pardomuan I, Samosir Regency Learning Year 2023/2024 Keywords:,